Difference in Sun Exposure Habits Between Individuals with High and Low Risk of Skin Cancer - Oskar Karlsson; Oskar Hagberg; Kari Nielsen; John Paoli; Åsa Ingvar (Mattioli1885, 2021)
Background: Skin cancer incidence is rapidly increasing. The main risk factor, sun exposure, can be modified. Informational campaigns can be effective in raising skin cancer awareness and target the high-risk population. Still, sun exposure habits in people at high risk of skin cancer are not well-known. Objective: To investigate if and how sun exposure habits differ between low-risk and high-risk individuals. Methods: During the Swedish Euromelanoma campaign of 2018, questionnaires were collected containing information regarding sun exposure habits and risk factors for skin cancer. Data on 4,141 participants was used to investigate the association between risk factors and sun exposure habits. Results: A fair skin type and a previous history of skin cancer were significantly associated with enhanced sun protective behavior. Family history of skin cancer, childhood sunburns and the presence of large/atypical nevi had no effect on sun exposure habits. Going on sunny holidays were particularly unaffected by being at high risk of skin cancer. Conclusion: Individuals at high risk of developing skin cancer showed suboptimal sun exposure habits and harmful traveling behaviors. We suggest that future skin cancer campaigns inform on accurate sun protection behavior during sunny holidays and associated risk factors. Risk factors such as childhood sunburns, numerous common and large/atypical nevi, as well as family history of skin cancer seem to be less recognized by the population.